2018
DOI: 10.3390/md16060216
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with a Magnesium-Rich Marine Mineral Blend Enhances the Diversity of Gastrointestinal Microbiota

Abstract: Accumulating evidence demonstrates that dietary supplementation with functional food ingredients play a role in systemic and brain health as well as in healthy ageing. Conversely, deficiencies in calcium and magnesium as a result of the increasing prevalence of a high fat/high sugar “Western diet” have been associated with health problems such as obesity, inflammatory bowel diseases, and cardiovascular diseases, as well as metabolic, immune, and psychiatric disorders. It is now recognized that modulating the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 82 publications
2
37
0
Order By: Relevance
“…Moreover, the discrepant results could be related to the hypervariable region that was analyzed [V3 or V3-V4] [4,[17][18][19] or the methods to evaluate intestinal microbiota, namely denaturation gradient gel electrophoresis [4,17], real-time quantitative PCR [18], or sequencing [4]. Additionally, the author who studied the same hypervariable region and performed the same massive sequencing as Crowley et al, suggests being cautious with the results, since the mineral mixture contained, in addition to magnesium, other trace minerals [18]. Moreover, the lower diversity observed with high dietary magnesium has also been observed in other minerals, such as zinc and iron.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the discrepant results could be related to the hypervariable region that was analyzed [V3 or V3-V4] [4,[17][18][19] or the methods to evaluate intestinal microbiota, namely denaturation gradient gel electrophoresis [4,17], real-time quantitative PCR [18], or sequencing [4]. Additionally, the author who studied the same hypervariable region and performed the same massive sequencing as Crowley et al, suggests being cautious with the results, since the mineral mixture contained, in addition to magnesium, other trace minerals [18]. Moreover, the lower diversity observed with high dietary magnesium has also been observed in other minerals, such as zinc and iron.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Vitamin D deficiency contributes to the pathogenesis of Crohn's disease and non-alcoholic fatty liver disease (NAFLD) and its supplementation has shown a positive effect in these patients and through regulating microbiome [61]. Moreover, magnesium deficiency has been shown to adversely affect gut microbial composition and to promote both anxiety and depressive-like behavior in mice [62]. Other studies in animal models have demonstrated that a high-fat diet decreases the number of bacterial species in the gut microbiome.…”
Section: Main Textmentioning
confidence: 99%
“…Upon supplementation of marine mineral blend, rich in bioactive calcium, magnesium, and 70 other trace minerals, bacterial species diversity increased, specifically increased levels of Proteobacteria were also noticed. 80 Therefore, seaweed and seawater-derived functional food may be considered as a reasonable supplement next to the high fat/high sugar "Western diet". In another study, phylum TM7, associated with IBD and Chron's disease, decreased in the group receiving lower concentration of the supplement, while Ruminococcaceae family associated with gut health increased for a group given a higher concentration of supplement.…”
Section: Insight Into Rat Intestinal Microbiota Modulation By Food Sumentioning
confidence: 99%
“…(Lachnospiraceae family) 37 Minerals Marine mineral blend (seaweed and seawater-derived, rich in bioactive calcium, magnesium and 70 other trace elements) (MMB) 30 7-8-week old male Sprague-Dawley rats n = 10, control group, standard chow n = 10, 0.1% MMB-supplemented chow n = 10, 0.2% MMB-supplemented chow Cecal content collected and stored at −80°C. 6 weeks DNA extraction using QIAmp Fast DNA Stool Mini Kit PCR Ilumina MiSeq sequencing platform QIIME ↑ diversity ↓ phylum TM7 (associated with IBD, Chron’s disease) in 0.1% MMB ↑ Proteobacteria (linked to inflammation and metabolic syndrome) in supplemented groups ↑ phylum RF3 in 0.2% MMB ↑ Ruminococcaceae, Clostridaceae (SCFA production) ↑ Christensenellaceae (lean BMI) ↑ Porphyromonadaceae (protective effect on gut health) 80 Methylxanthines Cocoa theobromine 21 3-week-old Lewis rats n = 7, reference group (RF) n = 7, standard diet with 10% of natural Forastero cocoa containing 0.25% theobromine (CC) n = 7, standard diet including 0.25% of theobromine (TB) Feces collected at d 0, 8, and 15, frozen at −20°C. 15 d Quantification of fecal microbiota by fluorescence in situ hybridization (FISH) coupled to flow cytometry (FCM) IgA-coated bacteria quantification metagenomics analysis: FastDNASPIN Kit 16 S rDNA sequencing in Ion Torrent platforms QIIME Greengenes reference database Theobromine group: FISH-FCM results: ↓ E. coli ↓ Bifidobacterium spp., Streptococcus spp., Clostridium histolyticum-C. perfringens ↓ Clostridium, Bacteroidaceae-Prevotellaceae ↓ Firmicutes metagenomics analysis : ↑ proportion of Tenericutes phylum ↑ proportion of the Erysipelotrichaceae family ( Firmicutes phylum), Ralstonia sp .…”
Section: Gut Microbiota Shifts In Healthy Rat Models By Different Nutmentioning
confidence: 99%